2012
DOI: 10.1002/ep.11705
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of trichloroethylene in anaerobic hybrid reactor

Abstract: In this study, anaerobic hybrid reactor (AHR) was intensively used for the treatment of synthetic wastewater containing trichloroethylene (TCE) by gradual increment in influent TCE and chemical oxygen demand (COD) concentrations. The acclimatization study revealed that 99.93 ± 0.13% and 97.81 ± 0.42% of TCE and COD could be removed at an influent TCE and COD concentrations of 50 and 2000 mg/L, respectively. The maximum yield coefficient (Ym) was found to be 0.05 mg biomass/mg COD, whereas the maximum specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Milia et al (Milia, Porcu et al, 2013) Mitra and Gupta (Mitra and Gupta, 2013) Zhu et al (Zhu, Lv et al, 2013) analyses the strains, identified as IP3-3(T) and SBP-1, were found to represent a novel species within the Dehalogenimonas genus. Both strains were able to reductively dehalogenate a number of chlorinated alkanes and alkenes when hydrogen gas was used as electron donor.…”
Section: Fenton/fentonmentioning
confidence: 99%
“…Milia et al (Milia, Porcu et al, 2013) Mitra and Gupta (Mitra and Gupta, 2013) Zhu et al (Zhu, Lv et al, 2013) analyses the strains, identified as IP3-3(T) and SBP-1, were found to represent a novel species within the Dehalogenimonas genus. Both strains were able to reductively dehalogenate a number of chlorinated alkanes and alkenes when hydrogen gas was used as electron donor.…”
Section: Fenton/fentonmentioning
confidence: 99%
“…Therefore, TCE causes dangers to ecology safety and human health. Moreover, the treatment of TCE has been investigated in aerobic reactors (Shukla et al 2009(Shukla et al , 2010 and some kinds of anaerobic reactors such as anaerobic hybrid reactor (Mitra and Gupta 2013) and expanded granular sludge bed (EGSB) bioreactors (Siggins et al 2011a, b); however, research about TCE treatment in the UASB reactor was limited (Ozdemir et al 2007). In addition, until now, there are few studies on the variations of bacterial community under different operation conditions of TCE treatment in the anaerobic reactors.…”
Section: Introductionmentioning
confidence: 98%